STAT3 methylation in white blood cells as a novel sensitive biomarker for the toxic effect of low-dose benzene exposure. Issue 3 (1st February 2016) - Liu, Di; Chen, Yujiao; Sun, Pengling; Bai, Wenlin; Gao, Ai
Graphical Abstract: Abstract: Alterations in DNA methylation patterns play an essential role in disease process and are associated with cancer risk. To explore the toxic effect and early sensitive biomarker of the health effects of low-dose benzene exposure (LDBE), and investigate the correlation between DNA methylation and the toxic effect of LDBE, a cross-sectional study was conducted in a sample of 571 workers; 312 workers who were exposed to a 1.82 ± 1.16 mg m −3 air benzene concentration were assigned to the LDBE group, while 259 non-known benzene exposure (NBE) workers were assigned to the control group, with an air benzene concentration of 0.06 ± 0.01 mg m −3 . Routine blood indexes, alanine transaminase (ALT), oxidative stress parameters and signal transducer and activator of transcription 3 (STAT3) methylation were detected. Compared with the NBE population, the STAT3 methylation level ( P = 0.001), Platelets (PLTs) ( P = 0.002) and 8-isoprostane-PGFs (8-iso-PGF2a) ( P = 0.001) manifested a significant reduction, while ALT ( P = 0.002) and 8-hydroxy-2 deoxyguanosine (8-OHdG) ( P = 0.002) showed a significant rise in the LDBE population. In addition, a significant correlation was observed between STAT3 methylation and oxidative stress, namely 8-OhdG and 8-iso-PGF2a. Furthermore, a multivariate analysis showed that the STAT3 methylation (structure loadings = 0.909) was the most strongly correlated with the other set of variables, especially with white blood cells (WBCs) (structure loadings = 0.675). Taken together, STAT3 methylation may be the underlying mechanism involved in the early toxic effect of LDBE, therefore, STAT3 methylation can be a novel sensitive biomarker for the toxic effect of low-dose benzene exposure.